2022
DOI: 10.1097/pgp.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Dataset for the Reporting of Carcinoma of the Cervix: Recommendations From the International Collaboration on Cancer Reporting (ICCR)

Abstract: Cervical carcinoma remains one of the most common cancers affecting women worldwide, despite effective screening programs being implemented in many countries for several decades. The International Collaboration on Cancer Reporting (ICCR) dataset for cervical carcinoma was first developed in 2017 with the aim of developing evidence-based standardized, consistent and comprehensive surgical pathology reports for resection specimens. This 4th edition update to the ICCR dataset on cervical cancer was undertaken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 164 publications
(310 reference statements)
0
14
0
1
Order By: Relevance
“…Because it was not based on HPV association, the pattern-based 2014 WHO classification of cervical SCCs was replaced in the 2020 WHO classification 1,4 ; the prognostic significance of various morphologic patterns (eg, keratinizing, nonkeratinizing, basaloid, warty/condylomatous, papillary, squamotransitional, and lymphoepithelial-like) was debated and determined to be not reproducible because of nonspecific definitions 4 . While the 2020 WHO classification does not recommend reporting histologic subtypes or growth patterns, we, along with the 2022 International Collaboration on Cancer Reporting (ICCR) guidelines, suggest this information remain in the surgical pathology report in a note or comment, given that primary tumor morphology is significant when looking for similarities to a recurrence 1,25,26 . This information could also be used in research to better understand the interplay between HPV infection, growth patterns, and clinical outcomes (Table 1).…”
Section: Human Papillomavirus-associated Squamous Cell Carcinomasmentioning
confidence: 98%
See 3 more Smart Citations
“…Because it was not based on HPV association, the pattern-based 2014 WHO classification of cervical SCCs was replaced in the 2020 WHO classification 1,4 ; the prognostic significance of various morphologic patterns (eg, keratinizing, nonkeratinizing, basaloid, warty/condylomatous, papillary, squamotransitional, and lymphoepithelial-like) was debated and determined to be not reproducible because of nonspecific definitions 4 . While the 2020 WHO classification does not recommend reporting histologic subtypes or growth patterns, we, along with the 2022 International Collaboration on Cancer Reporting (ICCR) guidelines, suggest this information remain in the surgical pathology report in a note or comment, given that primary tumor morphology is significant when looking for similarities to a recurrence 1,25,26 . This information could also be used in research to better understand the interplay between HPV infection, growth patterns, and clinical outcomes (Table 1).…”
Section: Human Papillomavirus-associated Squamous Cell Carcinomasmentioning
confidence: 98%
“…Finding that tumor type assignment (Supplemental Material, Supplemental Digital Content 1, http://links.lww.com/PAP/A34) is neither reproducible nor predictive of survival is consistent with previous studies that concluded this value has limited implications in SCCs. Consequently, removing these variables from the 2020 WHO classification and no longer recognizing them as core data in pathology reports are justified 1,26 …”
Section: Reproducibility Of Different Growth Patterns (Original Vs Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…After its first description in 2013, 1 the pattern‐based classification of HPV‐associated endocervical adenocarcinoma (HPVA) has been the subject of numerous studies, which have validated its role in predicting lymph node involvement, tumour recurrence and patient outcome 2–5 . The current National Comprehensive Cancer Network (NCCN) guidelines for the management of cervical cancer now include the pattern‐based classification for HPV‐associated endocervical adenocarcinoma (HPVA) as an emerging concept, 6 and the latest guidelines by the International Society of Gynaecological Pathologists 7 and the International Collaboration on Cancer Reporting 8 recommend including the invasive pattern in the diagnostic report.…”
Section: Introductionmentioning
confidence: 99%